2008
DOI: 10.1051/0004-6361:200809515
|View full text |Cite
|
Sign up to set email alerts
|

Molecular jets driven by high-mass protostars: a detailed study of the IRAS 20126+4104 jet

Abstract: Context. Protostellar jets from intermediate-and high-mass protostars provide an excellent opportunity to understand the mechanisms responsible for intermediate-and high-mass star-formation. A crucial question is if they are scaled-up versions of their low-mass counterparts. Such high-mass jets are relatively rare and, usually, they are distant and highly embedded in their parental clouds. The IRAS 20126+4104 molecular jet, driven by a 10 4 L protostar, represents a suitable target to investigate. Aims. We pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
84
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 53 publications
11
84
1
Order By: Relevance
“…This would lead to a precession period of about four years in order to generate the structures (A, B, and C) at each side of the so-called cavity (opening angle ∼65 • ). This period is too short when compared with typical jet fast precession periods (Rosen & Smith 2004;Caratti o Garatti et al 2008), and not consistent with the longer period suggested by the large-scale jet images (see f08-01 field in Khanzadyan et al 2004).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This would lead to a precession period of about four years in order to generate the structures (A, B, and C) at each side of the so-called cavity (opening angle ∼65 • ). This period is too short when compared with typical jet fast precession periods (Rosen & Smith 2004;Caratti o Garatti et al 2008), and not consistent with the longer period suggested by the large-scale jet images (see f08-01 field in Khanzadyan et al 2004).…”
Section: Discussioncontrasting
confidence: 61%
“…However, it is worth noting that these sources are likely to be more massive than ours. This suggests that (1) most of the outflow material is transported by a cooler and denser component than traced by the near-IR H 2 lines, such as the H 2 pure rotational lines (Caratti o Garatti et al 2008); or (2) most of the H 2 has been dissociated, and the jet is mainly atomic. The latter has been observed in other Class I jets, where the measuredṀ H 2 is around one order of magnitude lower than measured from the [Fe ii] emission (Davis et al 2011;Nisini et al 2005).…”
Section: Accretion and Ejection Propertiesmentioning
confidence: 99%
“…In particular, a correlation between outflow luminosity and the bolometric luminosity, L bol , of the driving source may exist. Such a correlation has been demonstrated for low-mass protostars and their outflows (Caratti o Garatti et al 2008); does this relationship extend towards intermediate and high-mass protostars? Unfortunately the current limited dataset for the driving sources in the Braid Nebula region (Table B.1) limits the accuracy of our L bol determinations, although additional observing campaigns are underway to fill the existing gaps in the source SEDs.…”
Section: Outflow Parametersmentioning
confidence: 85%
“…However, if one plots column densities derived from lines from only the first few vibrational states, a linear fit is usually quite adequate (e.g. Lorenzetti et al 2002;Giannini et al 2004;Davis et al 2004;Gredel 2006;Caratti o Garatti et al 2008;Martín-Hernández et al 2008). By minimising the scatter of points about this line, one can then estimate the extinction.…”
Section: Appendix A: the Effects Of Differential Refraction On Sourcementioning
confidence: 99%